No Ancient DNA Damage in Actinobacteria from the Neanderthal Bone - Zaremba-Niedźwiedzka, Katarzyna; Andersson, Siv G. E. (PLOS ONE, 2013)
Background The Neanderthal genome was recently sequenced using DNA extracted from a 38,000-year-old fossil. At the start of the project, the fraction of mammalian and bacterial DNA in the sample was estimated to be <6% and 9%, respectively. Treatment with restriction enzymes prior to sequencing increased the relative proportion of mammalian DNA to 15%, but the large majority of sequences remain uncharacterized. Principal Findings Our taxonomic profiling of 3.95 Gb of Neanderthal DNA isolated from the Vindija Neanderthal Vi33.16 fossil showed that 90% of about 50,000 rRNA gene sequence reads were of bacterial origin, of which Actinobacteria accounted for more than 75%. Actinobacteria also represented more than 80% of the PCR-amplified 16S rRNA gene sequences from a cave sediment sample taken from the same G layer as the Neanderthal bone. However, phylogenetic analyses did not identify any sediment clones that were closely related to the bone-derived sequences. We analysed the patterns of nucleotide differences in the individual sequence reads compared to the assembled consensus sequences of the rRNA gene sequences. The typical ancient nucleotide substitution pattern with a majority of C to T changes indicative of DNA damage was observed for the Neanderthal rRNA gene sequences, but not for the Streptomyces-like rRNA gene sequences. Conclusions/Significance Our analyses suggest that the Actinobacteria, and especially members of the Streptomycetales, contribute the majority of sequences in the DNA extracted from the Neanderthal fossil Vi33.16. The bacterial DNA showed no signs of damage, and we hypothesize that it was derived from bacteria that have been enriched inside the bone. The bioinformatic approach used here paves the way for future studies of microbial compositions and patterns of DNA damage in bacteria from archaeological bones. Such studies can help identify targeted measures to increase the relative amount of endogenous DNA in the sample.